2014
DOI: 10.1002/anie.201311150
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Poly(2‐methyloxazoline)s with Bioswitchable Activity through Satellite Group Modification

Abstract: Biocides are widely used for preventing the spread of microbial infections and fouling of materials. Since their use can build up microbial resistance and cause unpredictable long-term environmental problems, new biocidal agents are required. In this study, we demonstrate a concept in which an antimicrobial polymer is deactivated by the cleavage of a single group. Following the satellite group approach, a biocidal quaternary ammonium group was linked through a poly(2-methyloxazoline) to an ester satellite grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 40 publications
1
75
0
Order By: Relevance
“…This result agrees well with recently reported examples showing that hydrophilicity diminishes hemotoxicity and then increases selectivity [64,66,[72][73][74][75][76][77]. However, there has to be a correct balance between the hydrophilic and hydrophobic segments, since it has been also reported that the increase on hydrophobicity can lead to lower hemocytotoxicity [78,79]. Additionally, no differences were found between mono and biscationic side-chain tails.…”
Section: P(an-co-mta1) P(an-co-mta1-buisupporting
confidence: 92%
“…This result agrees well with recently reported examples showing that hydrophilicity diminishes hemotoxicity and then increases selectivity [64,66,[72][73][74][75][76][77]. However, there has to be a correct balance between the hydrophilic and hydrophobic segments, since it has been also reported that the increase on hydrophobicity can lead to lower hemocytotoxicity [78,79]. Additionally, no differences were found between mono and biscationic side-chain tails.…”
Section: P(an-co-mta1) P(an-co-mta1-buisupporting
confidence: 92%
“…Degradation or deactivation of the polymer after required therapeutic effect has been achieved is important to avoid the long-term environmental problems and to release in-active M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 degradation by-products. Tiller and co-workers reported antimicrobial polymers with degradable ester satellite group that possess bio-switchable activity [52]. We show that cyclization and optimum hydrophobicity of side chains in these amphiphilic polymers influence the selective toxicity to bacteria sparing the mammalian cells.…”
Section: A N U S C R I P Tmentioning
confidence: 69%
“…8) [99]. Cationic ring-opening polymerization of 2-methyl-2-oxazoline was used to prepare the polymer while termination with the biocidal group N,N-dimethyldodecylamine introduced antimicrobial activity (Table 4C).…”
Section: Telechelic Polymersmentioning
confidence: 99%